Reconstruction of the Principle of Legality in Law Number 1 of 2023: An Analysis of the Extension of Living Law in Society and Its Implications for Legal Certainty - Indah Cahya Purnama; Herlita Eryke (UNIVERSITAS PAKUAN, 2026)
This study examines the effect of the application of living law on legal certainty in Indonesia's criminal justice system after the enactment of Law Number 1 of 2023. The analysis is based on 412 court decisions from 2022 to 2025, comparing conditions before and after the reform . The findings show a significant increase in the intensity of living law application, reflected in higher references to local norms, stronger sociological reasoning, and greater influence on judicial decisions. At the same time, legal certainty declined, as indicated by reduced decision consistency, increased judging disparity, and higher rates of legal appeals . Regression results confirm that all indicators of living law application have a negative and significant effect on legal certainty. The strongest effect comes from the influence of living law on judicial decisions, followed by sociological reasoning and references to local norms . This study provides an empirical contribution to the literature on legal pluralism and criminal law reform by demonstrating how the expansion of non-written norms affects judicial consistency. The findings highlight the need for clear interpretative guidelines to ensure balance between flexibility and legal certainty. Keywords :​ Living law, legal certainty, criminal justice, sentencing disparity.